Pendampingan Belajar Membaca Alqur’an Pada Anak-Anak Warga Gang Sastro Dusun V Desa Bandar Setia - Ibrahim Hasan; Mavianti; Nila Sari (LPPI UMN AL WASHLIYAH, 2025)
This Community Service activity aims to illustrate the successful implementation of Quran reading assistance that has been taking place at the residence of residents in Gang Sastro, Dusun V, Desa Bandar Setia. This activity is expected to provide benefits and tangible contributions to the children in the area. The approach used is a guidance method through direct practice assistance in reading the Quran for children of standard elementary school age in Bandar Setia Village. Where in reading the Quran, children still experience many difficulties in pronouncing letters and reading rules, so they still need guidance. The main source of learning is the Quran. The results of this activity reveal that Quran literacy mentoring for the children of Gang Sastra residents, Dusun V, Desa Bandar Setia has a positive impact and makes a tangible contribution. The children showed enthusiasm in learning, were able to read hijaiyah letters accurately, place harakat according to the rules, understand the rules of Quranic recitation according to tajwid principles, and could practice them correctly according to the guidance and instructions of the mentors.